Costa Rica : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Costa Rica. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The Costa Rican economy has grown at rapid rates in the last three years, underpinned by a robust world expansion, sound economic policies, and strong business and consumer confidence. Economic policies have been well oriented. The fiscal position has substantially improved. The exchange rate level and policies are consistent with the maintenance of external stability. IMF staff supports the neutral policy stance envisaged in the 2008 central government budget and plans for a substantive tax reform. The authorities should push ahead with financial system reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet